2008
DOI: 10.1063/1.2987169
|View full text |Cite
|
Sign up to set email alerts
|

Perspectives on heavy-quarkonium production at the LHC

Abstract: We summarise the perspectives on heavy-quarkonium production at the LHC, both for proton-proton and heavy-ion runs, as emanating from the round table held at the HLPW 2008 Conference. The main topics are: present experimental and theoretical knowledge, experimental capabilities, open questions, recent theoretical advances and potentialities linked to some new observables.Comment: Summary of the round table on quarkonium production held at the Joint Meeting Heidelberg-Liege-Paris-Wroclaw: Three Days of Strong… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0

Year Published

2008
2008
2018
2018

Publication Types

Select...
7
1

Relationship

5
3

Authors

Journals

citations
Cited by 33 publications
(14 citation statements)
references
References 100 publications
0
14
0
Order By: Relevance
“…The ATLAS experiment [31] at the LHC is a multi-purpose detector with a forward-backward symmetric cylindrical geometry and a nearly 4π coverage in solid angle. 1 It consists of an inner tracking detector (ID) surrounded by a thin superconducting solenoid providing a 2 T axial magnetic field, electromagnetic and hadron calorimeters, and a muon spectrometer (MS). The ID covers the pseudorapidity range |η| < 2.5.…”
Section: Atlas Detectormentioning
confidence: 99%
See 1 more Smart Citation
“…The ATLAS experiment [31] at the LHC is a multi-purpose detector with a forward-backward symmetric cylindrical geometry and a nearly 4π coverage in solid angle. 1 It consists of an inner tracking detector (ID) surrounded by a thin superconducting solenoid providing a 2 T axial magnetic field, electromagnetic and hadron calorimeters, and a muon spectrometer (MS). The ID covers the pseudorapidity range |η| < 2.5.…”
Section: Atlas Detectormentioning
confidence: 99%
“…The study of heavy quarkonium bound states (cc and bb) in ultra-relativistic heavy-ion collisions [1,2] has been a subject of intense theoretical and experimental efforts since it was initially proposed by Matsui and Satz [3] as a probe to study a deconfined quark-gluon plasma (QGP) created in nucleus-nucleus (A+A) collisions. In order to understand quarkonium yields in A+A collisions it is necessary to disentangle effects due to interaction between quarkonium and the QGP medium from those that can be ascribed to cold nuclear matter (CNM).…”
Section: Introductionmentioning
confidence: 99%
“…There have been numerous experimental and theoretical investigations since then that have demonstrated that other effects are also present in addition to colour screening in a deconfined plasma [ 4 6 ]. First, it has been shown that over a wide range of interaction energies there is already a modification in the production of mesons in systems where a large volume of quark–gluon plasma does not appear to form, such as in proton–nucleus collisions [ 7 – 9 ].…”
Section: Introductionmentioning
confidence: 99%
“…By extension, available theoretical predictions for the production rates at the LHC are rather uncertain. For recent reviews, the reader is guided to [1,2,3] along with some perspectives for the LHC [4].…”
Section: Introductionmentioning
confidence: 99%